Pembelajaran Organisasi di Pondok Pesantren - Nurhadi, Nurhadi (Institut Agama Islam Negeri (IAIN) Tulungagung, 2013)
Pesantren as social religious organization plays important role in implementing the concept of education for all. Such concept accommodates the belief that every human being holds a right to be educated either formally or informally. The implication is throughÂ pesantren, somebody may learn to live a life well. Further, pesantren is responsible to develop its students to become intelligent and pious.